Efektifitas Pijat Perineum Dalam Mencegah Terjadinya Laserasi Perineum dan Episiotomi Pada Persalinan Normal di BPM. Sri Wahyuni Surabaya: The Effectiveness of Perineal Massage in Preventing Perineal Laceration and Episiotomy in Normal Delivery in BPM. Sri Wahyuni ​​Surabaya - Marifah, Umi (Jurnal Kebidanan Midwiferia, 2017)
One of the fears that are often perceived by the third trimester pregnant women that their perineal laceration during delivery. The soft tissues and structures around the perineum will be damaged. The damage is usually more common in primipara. Results of a preliminary study on BPM. Sri Wahyu Surabaya primigravid there are 78 people who gave birth in January to March 2015, the number of mothers who undergo perineal laceration many as 64 people (82%). One effort to prevent perineal lacerations that massage the perineum. Perineal massage is a massage technique perineum start 34/35 weeks gestation until just before delivery to increase blood flow and increases the elasticity of the perineum. The study aims to analyze the effectiveness of perineal massage in preventing perineal lacerations and episiotomy in normal labor in BPM. Sri Wahyu Surabaya. The study was conducted for 8 months. The study design is Static-Group Comparison of design population is primigravida in BPM. Sri Wahyu Surabaya as many as 44 people. The research sample using techniques Quota sampling as many as 40 people consisting of a control group of 20 people and the treatment group of 20 people. The results of the analysis of Fisher's Exact test showed the value of p = 0.000 (<0.05), then massage the perineum affect the occurrence of perineal lacerations in normal labor between the intervention and control groups, so that perineal massage can be applied mainly on primigravidae to prevent episiotomy in normal labor.